Pengaruh Servant Leadership Terhadap Keinginan Genenerasi Z Berpindah Pekerjaan - Yurdi Maulidani; Reza Luqman Hakim; Bejo Santoso; Riduansah Riduansah; Saiful Saiful (Penerbit Goodwood, 2025)
Purpose: This study aims to deepen the understanding of the influence of servant leadership on turnover intention, with a case study focused on Generation Z employees in micro enterprises in Samarinda City. Methodology: This study is a causal research aimed at testing the influence of servant leadership on turnover intention among Generation Z employees working in micro enterprises in Samarinda City. The research method used is PLS-SEM, with 65 respondents. Results: Servant leadership can significantly reduce the intention of Generation Z to switch jobs. This means that the stronger the application of leadership principles focused on service, empathy, and employee empowerment, the lower the tendency of Generation Z to leave their jobs. Additionally, it was found that servant leadership can explain 37.00% of the variation in turnover intention. Limitations: This study focuses only on Generation Z employees in micro-enterprises in Samarinda City, with fewer than 100 respondents, so it cannot be used as a sufficiently strong basis to explain the behavior of Generation Z employees in general across different types of businesses. Contribution: This study found that a leadership style that prioritizes employee well-being and the development of positive interpersonal relationships can be an effective strategy in increasing loyalty and reducing turnover intention, particularly among the younger workforce, who tend to switch jobs more easily.